Superoxide reductase from the syphilis spirochete Treponema pallidum: crystallization and structure determination using soft X-rays - Santos-Silva, Teresa (2019)
Superoxide reductase is a 14 kDa metalloprotein containing a catalytic non-haem iron centre [Fe(His)4Cys]. It is involved in defence mechanisms against oxygen toxicity, scavenging superoxide radicals from the cell. The oxidized form of Treponema pallidum superoxide reductase was crystallized in the presence of polyethylene glycol and magnesium chloride. Two crystal forms were obtained depending on the oxidizing agents used after purification: crystals grown in the presence of K3Fe(CN)6 belonged to space group P21 (unit-cell parameters a = 60.3, b = 59.9, c = 64.8 Å, β = 106.9°) and diffracted beyond 1.60 Å resolution, while crystals grown in the presence of Na2IrCl 6 belonged to space group C2 (a = 119.4, b = 60.1, c = 65.6 Å, β = 104.9°) and diffracted beyond 1.55 Å. A highly redundant X-ray diffraction data set from the C2 crystal form collected on a copper rotating-anode generator (λ = 1.542 Å) clearly defined the positions of the four Fe atoms present in the asymmetric unit by SAD methods. A MAD experiment at the iron absorption edge confirmed the positions of the previously determined iron sites and provided better phases for model building and refinement. Molecular replacement using the P21 data set was successful using a preliminary trace as a search model. A similar arrangement of the four protein molecules could be observed.